A comparative study of laparoscopic cholecystectomy with and without abdominal drain - Gadhvi, Udit I.; Bhimani, Dhaval A.; Waghela, Jaivik; Rajgor, Darshil K. (International Journal of Research in Medical Sciences, 2018)
Background: Laparoscopic surgery has several advantages when compared to open surgery, including faster post-operative recovery and lower pain scores. Laparoscopic cholecystectomy is the main method of treatment of symptomatic gallstones. Routine drainage after laparoscopic cholecystectomy is an issue of considerable debate. Methods: Study was randomized, prospective, observational and longitudinal including 100 patients, selected according to inclusion criteria. Results: The sub hepatic fluid collection on first ultrasound at 24hrs was higher in drained group than in non-drained groups. Further, the difference became insignificant on subsequent ultrasound at 72hrs. Incidence of post-operative drain site pain was present in 25% of patients with drain (more at drain site). Incidence drain site infection was present in 16.6% of patients in drain group. Majority of the patients with drain group (n=24) required hospital stay for ≥3 days, while for majority of patients without drain group (n=20), required hospital stay was 1 day. Conclusions: An uncomplicated gall stone disease can be treated by laparoscopic cholecystectomy without need for drain with reasonable safety by an experienced surgeon. With no usage of drain, it is significantly advantageous in terms of post-operative pain, use of analgesics and hospital stay.